Characteristics of catechin loading rice porous starch/chitosan functional microsphere and its adsorption towards Pb2+ - Suwei Jiang; Hailiang Hu (Heliyon, 2022)
In this paper, we explore the adsorption potential of catechin (CT) loaded composite microspheres and provide a new micron scale carrier of functional factor. Chitosan (CS) modified rice porous starch (RPS/CS) was used as a CT adsorption carrier to prepare bioactive CT-loaded composite microspheres (CT@RPS/CS). The adsorption kinetics, storage characteristics, and biological activity maintenance of CT@RPS/CS were studied in an aqueous solution, and the sustained-release characteristics of CT@RPS/CS were studied in vitro during simulated gastrointestinal digestion. An aqueous solution further studied the removal characteristics of adsorbed heavy metal ion Pb2+. RPS/CS can significantly improve the ability to adsorb CT. RPS/CS can also significantly improve CT's storage stability, antioxidant stress, and slow-release characteristics, and the sustained release effect in gastric and intestinal juice. CT@RPS/CS can be removed Pb2+ by adsorbing in the solution, and their adsorption was physical adsorption and chemisorption, but the primary interaction is chemisorption. CT@RPS/CS can be used as a micron carrier of new food functional factors, which has potential space for improving and expanding the functional characteristics of its loaded functional factors and the endowing of new functions.